Nursing habits and early childhood caries in children attending Hospital University Science Malaysia (HUSM) - Widowati Witjaksono; Mon Mon Tin Oo; Khamisah Awang Kechik (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2006)
The habit of nocturnal bottle or breast-feeding has been reported to be a potential cause for early childhood caries (ECC) in very young children. The aim of this study was to determine the prevalence of ECC in children 2-5 years of age attending out patient clinic HUSM, in relation to the nursing habits. In this cross-sectional study, 90 children were randomly selected to examine their caries status using torch and disposable mirror. Data on mothers’ educational level, nursing habits and oral hygiene practices, were gather by using structured questionnaire. It has been found that 16.7% of subjects were caries free while 83.3% of them had caries with mean dmf score 6 (SD 5.3). With regard to nursing habits, 29% of subjects had breast-feeding alone, 16% had bottle-feeding alone and 55% had both breast and bottle-feeding. Ninety-three percent of children had been nursed beyond 14 months and 47% had been fed with liquids other than breast milk, infant formula or water. Twenty-seven percent of children were allowed to sleep with nursing bottle in mouth and 52% were allowed to sleep with breast nipple in the mouth which shows significantly associated with ECC (p = 0.03). Tooth brushing habit was reported for 91% of children using toothpaste. Mean age of the children (in months) when the mothers started brushing the teeth was 19.1 (SD 10.8) and has significant association with ECC (p < 0.05). This study demonstrates that the habit of allowing infants to sleep with breast nipple in their mouth and the late start of tooth brushing are associated with prevalence of ECC. Educational programs for pregnant women and mothers of young children should be emphasized to enhance the knowledge and awareness of mothers in preventing ECC.